A porous carbon nanotube-supported high entropy alloy and its preparation method and application
By uniformly distributed high -entropy -like hydrogen oxide nanoscopic tablets on the surface of the carbon nanotuba to form porous nano -flower network catalysts, the high cost, environmental problems and scarcity problems of traditional precious metal catalysts in the analysis of oxygen analysis have been solved. High -efficiency and stable electrolytic oxygen reaction.
Patent Information
- Application Number
- CN202410249464.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-05
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-03-05
AI Technical Summary
Traditional precious metal catalysts have high costs, environmental problems and scarcity in oxygen evolution reactions, which are difficult to widely use, and the reaction kinetics are slow, resulting in high overpotentials and limiting the efficiency of electrolytic water.
Using porous carbon nanopolytic support high entropy alloys (Fealnicomn-He-LDH/CNT), a high-entropy layer-like hydrogen oxide nanosometer is evenly distributed on the surface of the carbon nanotuba through the water heat synthesis method, forming a porous nano-flower network catalyst, which is significant Increase surface area and electrochemical catalytic activity.
It improves the activity and stability of the catalyst, reduces the potential, enhances oxygen analysis efficiency, and maintains good electrocatalytic performance at high current density, which lasts for a long time.
Smart Images

Figure CN118109864B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical catalysts, and in particular relates to a porous carbon nanotube-supported high-entropy alloy and a preparation method and application thereof. Background Art
[0002] The oxygen evolution reaction (OER) is a key process in electrochemical water splitting. Since the OER oxygen evolution reaction is a four-electron transfer process, its mechanism is very complex and the reaction kinetics are slow, resulting in a high overpotential, which is a key factor limiting the efficiency of water electrolysis.
[0003] Because high overpotential and slow kinetics slow the rate of the oxygen evolution reaction (OER), the use of catalysts is crucial to improving its rate. Traditional catalysts are primarily made from precious metals (such as IrO2), but their use is limited by high cost and environmental concerns. Furthermore, the scarcity of precious metals prevents their widespread application.
[0004] Currently, high-entropy alloys (HEAs), as alternatives to noble metals, exhibit the stability and diverse catalytic sites required for OER. These HEAs offer a unique combination of properties (including their diverse elemental composition), resulting in strong catalytic activity and stability.
[0005] Therefore, it is necessary to develop a high-entropy alloy with strong catalytic activity and stability. Summary of the Invention
[0006] In response to the above problems, the purpose of the present invention is to provide a porous carbon nanotube-supported high-entropy alloy, which uses multi-walled carbon nanotubes as the supporting material of the high-entropy alloy to form a porous nanoflower network catalyst, which significantly increases the surface area and improves the electrochemical catalytic activity.
[0007] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0008] On the one hand, the present invention provides a porous carbon nanotube-supported high-entropy alloy, which is a porous nanoflower network structure; the nanosheet structure formed by iron, aluminum, nickel, cobalt and manganese elements is evenly distributed on the surface of the multi-walled carbon nanotube; and the average pore diameter of the porous carbon nanotube-supported high-entropy alloy is 10nm-11nm, and the average pore volume is 0.25cm 3 / g-0.3cm 3 / g, specific surface area of 50m 2 / g-54m 2 / g, and the effective surface area of the double layer capacitor is 6.2mF / cm 2 -6.5mF / cm 2 , the Tafel slope is 46mV / dec-47mV / dec.
[0009] On the other hand, the present invention provides a method for preparing a porous carbon nanotube-supported high-entropy alloy, which comprises: (1) mixing a multi-walled carbon nanotube dispersion with a mixed metal salt to obtain a mixed solution, wherein the mixed metal salt is composed of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate; (2) mixing the mixed solution, urea and ammonium fluoride to obtain a reaction precursor solution; and (3) subjecting the reaction precursor solution to a hydrothermal reaction at 110° C.-150° C. to obtain a porous carbon nanotube-supported high-entropy alloy.
[0010] Preferably, the multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion may be oxidized multi-walled carbon nanotubes.
[0011] Preferably, the molar ratio of the mixed metal salt to urea may be (5.8-6.2):1, and the molar ratio of the mixed metal salt to NH4F may be (2.3-2.7):1.
[0012] Preferably, in the mixed solution, the molar concentrations of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate may be 0.5 mmol / L-1 mmol / L.
[0013] Preferably, in the mixed metal salt, iron nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate may be in equimolar amounts.
[0014] Preferably, the mass ratio of the multi-walled carbon nanotubes to the mixed metal salt can be 1:(50-80).
[0015] Preferably, the hydrothermal reaction time can be 10 h-18 h.
[0016] Preferably, the above preparation method may further include a purification step, which comprises: washing the porous carbon nanotube-supported high-entropy alloy obtained by the hydrothermal reaction with a detergent, and then vacuum drying it in a vacuum drying oven at 40°C-60°C for 10h-15h.
[0017] In another aspect, the present invention provides the use of the porous carbon nanotube-supported high entropy alloy described above or the porous carbon nanotube-supported high entropy alloy prepared by the method for preparing the porous carbon nanotube-supported high entropy alloy as a catalyst in oxygen evolution reaction by electrolysis of water.
[0018] The beneficial effects of the present invention include at least:
[0019] (1) The specific surface area of the porous carbon nanotube-supported high entropy alloy (FeAlNiCoMn-HE-LDH / CNT) provided by the present invention can reach 52.40 m 2 / g or more, which is better than high-entropy alloys without carbon nanotube support, and can provide more electrochemical catalytic active sites as much as possible, thereby improving the activity of the catalyst.
[0020] (2) The porous carbon nanotube-supported high-entropy alloy provided by the present invention has a lower overpotential, which is lower than that of the high-entropy alloy without carbon nanotube support (FeAlNiCoMn-HE-LDH) and the noble metal oxygen evolution catalyst iridium dioxide IrO2; the current density increase is the lowest, which is lower than that of IrO2 and FeAlNiCoMn-HE-LDH, indicating that FeAlNiCoMn-HE-LDH / CNT has significant oxygen evolution efficiency.
[0021] (3) The porous carbon nanotube-supported high entropy alloy provided by the present invention has a small Tafel slope (46.65 mV / dec), strong OER activity, and a large double-layer capacitance effective surface area (6.21 mF / cm 2 ) and has the fastest electron transfer reaction rate, that is, it has strong electrocatalytic activity.
[0022] (4) The porous carbon nanotube-supported high entropy alloy provided by the present invention has excellent stability at 150 mA cm -2 At an extremely high current density of 1.5 Å, its electrocatalytic performance remains good for an ultra-long duration of about 240 hours.
[0023] (5) The preparation method of the porous carbon nanotube-supported high-entropy alloy provided by the present invention uses a hydrothermal synthesis method, which can be carried out at 150°C or below, avoiding the high temperature of the traditional method and reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the scanning electron microscope (SEM) image of carbon nanotubes;
[0025] Figure 2 This is the scanning electron microscope (SEM) image of FeAlNiCoMn-HE-LDH / CNT;
[0026] Figure 3 EDS and EDX element maps of FeAlNiCoMn-HE-LDH / CNT;
[0027] Figure 4 TEM images of FeAlNiCoMn-HE-LDH / CNT, where (a) is the high-resolution transmission electron microscope (HRTEM) image; (b) is the inverse of FFT; (c) is the d spacing;
[0028] Figure 5 HAADF-STEM images of FeAlNiCoMn-HE-LDH / CNT, where (a) is high-angle annular dark field imaging (HAADF-STEM); (b) is selected area electron diffraction (SAED);
[0029] Figure 6 This is the scanning electron microscope (SEM) image of FeAlNiCoMn;
[0030] Figure 7 This is a scanning electron microscope (SEM) image of AlNiCoMn;
[0031] Figure 8 This is the scanning electron microscope (SEM) image of AlNiCo;
[0032] Figure 9 This is the scanning electron microscope (SEM) image of AlNi;
[0033] Figure 10 This is the scanning electron microscope (SEM) image of FeNi;
[0034] Figure 11 is the X-ray diffraction pattern of each sample;
[0035] Figure 12 Nitrogen isothermal adsorption-desorption curves and BET specific surface area diagrams of each sample;
[0036] Figure 13 LSV diagram for OER performance test of each sample;
[0037] Figure 14 is the linear sweep voltammetry (LSV) curve of each sample;
[0038] Figure 15 is the Tafel slope of each sample;
[0039] Figure 16 is the electrochemical impedance spectrum of each sample;
[0040] Figure 17 is the effect of the scan rate of each sample (pH is 13-14);
[0041] Figure 18 These are the stability test results of FeAlNiCoMn-HE-LDH / CNT (pH is 13-14). DETAILED DESCRIPTION
[0042] The examples are provided to better illustrate the present invention, but are not intended to limit the present invention to the examples. Therefore, non-essential improvements and adjustments to the embodiments made by those skilled in the art based on the above-mentioned invention still fall within the scope of protection of the present invention.
[0043] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "comprise" and the like are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0044] The embodiment of the present invention provides a porous carbon nanotube-supported high-entropy alloy, which is a porous nanoflower network structure; the nanosheet structure formed by iron, aluminum, nickel, cobalt and manganese elements is evenly distributed on the surface of the multi-walled carbon nanotube; and the average pore diameter of the porous carbon nanotube-supported high-entropy alloy is 10nm-11nm, and the average pore volume is 0.25cm 3 / g-0.3cm 3 / g, specific surface area of 50m 2 / g-54m 2 / g, and the effective surface area of the double layer capacitor is 6.2mF / cm 2 -6.5mF / cm 2 , the Tafel slope is 46mV / dec-47mV / dec.
[0045] It should be noted that the porous carbon nanotube-supported high-entropy alloy in the present invention is a porous nanoflower network formed by combining carbon nanotubes and HEAs. This porous nanoflower network structure provides more active sites and contributes to better gas release, and significantly increases the surface area to improve electrochemical catalytic activity. In addition, as long as the porous carbon nanotube-supported high-entropy alloy in the present invention meets the above-mentioned structural description, and the average pore size, average pore volume, specific surface area, double-layer capacitance effective surface area and Tafel slope meet the above requirements, the technical effects of the present invention can be achieved, meeting industrial production needs.
[0046] It should also be noted that the porous carbon nanotube-supported high-entropy alloys of the present invention exhibit higher electrochemical catalytic activity and better stability than those without carbon nanotube support. Furthermore, the carbon nanotubes enhance the active surface area of the catalyst, providing excellent electrical conductivity and structural durability, which are crucial for efficient electron transfer and stability under the harsh conditions of the OER.
[0047] Another embodiment of the present invention provides a method for preparing a porous carbon nanotube-supported high-entropy alloy, which comprises: (1) mixing a multi-walled carbon nanotube dispersion with a mixed metal salt to obtain a mixed solution, wherein the mixed metal salt is composed of iron nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate; (2) mixing the mixed solution with urea and ammonium fluoride to obtain a reaction precursor solution; and (3) subjecting the reaction precursor solution to a hydrothermal reaction at 110° C.-150° C. to obtain a porous carbon nanotube-supported high-entropy alloy.
[0048] It should be noted that existing methods for synthesizing high-entropy alloys primarily include sputtering, arc melting, and plasma sintering. These methods are limited by high temperatures, high costs, and low equipment yields, hindering their large-scale application in water electrolysis. The present invention utilizes a hydrothermal synthesis method that can be performed at temperatures of 150°C or below, avoiding the high temperatures of traditional methods, reducing energy consumption, and minimizing material degradation. Furthermore, temperatures below 110°C do not fully react, so a temperature between 110°C and 150°C is preferred in the present invention.
[0049] It should also be noted that urea and ammonium fluoride are added as a kind of "surfactant" to affect the morphology of the resulting crystals (i.e., plate-like) so that the metal salt tends to form an LDH morphology during the hydrothermal reaction, thereby obtaining a porous carbon nanotube-supported high-entropy alloy.
[0050] In some specific embodiments, the multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion may be oxidized multi-walled carbon nanotubes. It should be noted that chemical oxidation of the carbon nanotube surface can also be used to impart a higher defect density to the carbon nanotube surface, thereby successfully growing high-entropy layered double hydroxides on the carbon nanotube surface, exhibiting exceptional oxygen evolution catalytic activity.
[0051] In some specific embodiments, the molar ratio of the mixed metal salt to urea can be (5.8-6.2):1, and the molar ratio of the mixed metal salt to NH4F can be (2.3-2.7):1. It should be noted that the molar ratio of the mixed metal salt to urea can be 5.9:1, 6:1 and 6.1:1, among which 6:1 is preferred. At this ratio, the prepared porous carbon nanotube-supported high entropy alloy has the best catalytic activity; in addition, the molar ratio of the mixed metal salt to NH4F can be 2.4:1, 2.5:1 or 2.6:1, among which 2.5:1 is preferred. At this ratio, the prepared porous carbon nanotube-supported high entropy alloy has the best catalytic activity; it should also be noted that when the molar ratio of the mixed metal salt to urea is 6:1 and the molar ratio of the mixed metal salt to NH4F is 2.5:1, the prepared porous carbon nanotube-supported high entropy alloy has the best catalytic activity.
[0052] In some specific embodiments, the molar concentrations of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and aluminum nitrate in the above-mentioned mixed solution can be 0.5 mmol / L-1 mmol / L, such as 0.6 mmol / L-0.9 mmol / L, 0.7 mmol / L-0.8 mmol / L, or 0.7 mmol / L-0.9 mmol / L. It should be noted that the molar concentrations of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and aluminum nitrate can be the same or different; in addition, if the molar concentrations of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and aluminum nitrate are lower than 0.5 mmol / L or higher than 1 mmol / L, an unbalanced crystal phase structure will appear, which will eventually lead to changes in the properties of the high-entropy alloy.
[0053] In some specific embodiments, the mixed metal salts include ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and aluminum nitrate in equimolar amounts. It should be noted that the amounts of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and nitric acid affect the properties of the resulting high-entropy alloy, with equimolar amounts of ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and aluminum nitrate being preferred. When these equimolar amounts are used, the resulting porous carbon nanotube-supported high-entropy alloy exhibits the best catalytic activity and stability.
[0054] In some specific embodiments, the mass ratio of the above-mentioned multi-walled carbon nanotubes to the mixed metal salt can be 1:(50-80), such as 1:55, 1:60, 1:65, 1:70 or 1:75, among which, when the mass ratio of the multi-walled carbon nanotubes to the mixed metal salt is 1:65, the catalytic activity and stability of the prepared porous carbon nanotube-supported high-entropy alloy are the best.
[0055] In some specific embodiments, the hydrothermal reaction time can be 10 hours to 18 hours. It should be noted that the preparation time of the porous carbon nanotube-supported high-entropy alloy in the present invention is preferably 10 hours to 18 hours. If it is less than 10 hours, the reaction is incomplete, and if it is more than 18 hours, the reaction rate is very slow and there is no significant increase.
[0056] In some specific embodiments, the above-mentioned preparation method may further include a purification step, which comprises: washing the porous carbon nanotube-supported high entropy alloy obtained by the hydrothermal reaction with a detergent, and then vacuum drying it in a vacuum drying oven at 40°C-60°C for 10h-15h. It should be noted that the porous carbon nanotube-supported high entropy alloy prepared in the present invention can be further washed and dried to obtain a purified porous carbon nanotube-supported high entropy alloy, and washing and drying are both conventional means in the art. Drying is preferably carried out in a vacuum drying oven at 40°C-60°C for 10h-15h, which can be better dried in the shortest time.
[0057] In some specific embodiments, the method for preparing a porous carbon nanotube-supported high entropy alloy may preferably include:
[0058] (1) chemically oxidizing carbon nanotubes by dispersing 0.3 g to 0.5 g of carbon nanotubes in 25 ml of an etching solution (a mixture of 96 wt% sulfuric acid and 30 wt% hydrogen peroxide in a volume ratio of 70:30). After oxidation for 5 hours, the resulting dispersion was diluted with water and filtered. The resulting solid was then washed to a neutral pH and the sample was vacuum dried at 40° C. overnight to obtain oxidized carbon nanotubes.
[0059] (2) ultrasonically treating the oxidized carbon nanotubes for 15-30 minutes to disperse them in water to obtain a dispersion, then adding ferric nitrate, nickel nitrate, cobalt nitrate, manganese nitrate, and aluminum nitrate to the dispersion and dissolving them to obtain a mixture, wherein the amount of metal salt used is 0.5 mmol / L-1 mmol / L, and stirring for 30 minutes to fully impregnate the chemically oxidized carbon nanotubes to obtain a multi-metallic carbon nanotube solution;
[0060] (3) adding urea and ammonium fluoride to the obtained multi-metal carbon nanotube mixed solution, with the ratio of urea to the total amount of metal salt being 1:(0.14-0.3) and the ratio of ammonium fluoride to the total amount of metal salt being 1:(0.2-0.5), and stirring for 30 minutes to obtain a reaction precursor liquid;
[0061] (4) The precursor liquid is placed in a hydrothermal reactor and reacted at 110°C-150°C for 10h-18h. After the reaction is completed, it is naturally cooled to room temperature to obtain a crude product of porous carbon nanotube-supported high-entropy alloy.
[0062] (5) The prepared porous carbon nanotube-supported high-entropy alloy crude product was centrifugally washed with 50 wt% ethanol, and the purified porous carbon nanotube-supported high-entropy alloy was obtained after drying.
[0063] Another embodiment of the present invention provides the use of any of the above-mentioned porous carbon nanotube-supported high-entropy alloys or the porous carbon nanotube-supported high-entropy alloys prepared by the above-mentioned preparation method of the porous carbon nanotube-supported high-entropy alloy as a catalyst in the oxygen evolution reaction of water electrolysis.
[0064] In order to better understand the present invention, the content of the present invention is further explained below with reference to specific examples, but the content of the present invention is not limited to the following examples.
[0065] 1. Preparation / Source of Samples
[0066] Example 1
[0067] (1) Weigh 0.3g of carbon nanotubes (electron microscopy images as shown in Figure 2) Figure 1The obtained carbon nanotubes were dispersed in 25 ml of an etching solution (a mixture of 96 wt % sulfuric acid and 30 wt % hydrogen peroxide in a volume ratio of 70:30) and oxidized for 5 hours. The obtained dispersion was diluted with water and filtered. The obtained solid was then washed to a neutral pH, and the sample was vacuum-dried at 40° C. overnight to obtain oxidized carbon nanotubes.
[0068] (2) Weigh 20 mg of the oxidized carbon nanotubes obtained in step (1) into a 50 ml beaker, and then add 1.2 mmol each of Fe(NO3)3·9H2O, Ni(NO3)3·6H2O, Co(NO3)2·6H2O, Mn(NO3)2·4H2O, and Al(NO3)3·9H2O to the beaker in batches to fully mix the oxidized carbon nanotubes and form a multi-metal carbon nanotube mixed solution;
[0069] (3) adding urea and ammonium fluoride to the obtained multi-metal carbon nanotube mixed solution, wherein the molar ratio of the mixed metal salt to urea is 6:1, and the molar ratio of the mixed metal salt to NH4F is 2.5:1, and stirring for 30 minutes to obtain a reaction precursor liquid;
[0070] (4) placing the precursor liquid in a hydrothermal reactor at 130° C. for 15 h, and naturally cooling to room temperature after the reaction to obtain a porous carbon nanotube-supported high entropy alloy (double hydroxide-LDH) composite catalyst intermediate;
[0071] (5) The product was centrifugally washed with 50 wt% ethanol and dried to obtain a porous carbon nanotube-supported high entropy alloy (double hydroxide-LDH) composite catalyst, which was labeled as HE-LDH / CNT (FeAlNiCoMn-HE-LDH / CNT).
[0072] Comparative Example 1
[0073] Compared with Example 1, the only difference of Comparative Example 1 is that no carbon nanotubes are added in step 1, and the other processes are the same as those in Example 1. The prepared product is marked as HE-LDHs (FeAlNiCoMn-LDHs).
[0074] Comparative Example 2
[0075] Comparative Example 2 is compared with Comparative Example 1, the difference of Comparative Example 2 is that Fe(NO3)3·9H2O is not added; the other processes are the same as those in Example 1, and the prepared product is marked as AlNiCoMn (also known as AlNiCoMn-HE-LDH / CNT).
[0076] Comparative Example 3
[0077] Comparative Example 3 is compared with Comparative Example 2. The difference between Comparative Example 2 and Comparative Example 3 is that Mn(NO3)2·6H2O is not added; the other processes are the same as those in Example 1, and the prepared product is marked as AlNiCo (also known as AlNiCo-HE-LDH / CNT).
[0078] Comparative Example 4
[0079] Comparative Example 4 is compared with Comparative Example 3. The difference between Comparative Example 3 and Comparative Example 4 is that Co(NO3)2·6H2O is not added; the other processes are the same as those in Example 1, and the prepared product is marked as AlNi (also known as AlNi-HE-LDH / CNT).
[0080] Comparative Example 5
[0081] Compared with Comparative Example 1, Comparative Example 5 does not add Co(NO3)2·6H2O, Mn(NO3)2·4H2O and Al(NO3)3·9H2O; other processes are the same as those in Example 1, and the prepared product is marked as FeNi (also known as FeNi--HE-LDH / CNT).
[0082] Comparative Example 6
[0083] The commercial precious metal oxygen evolution catalyst iridium dioxide IrO2 is from Merck Sidrich.
[0084] Comparative Example 7
[0085] Nickel metal foam (Bare NF) was obtained from Merck Sidrich.
[0086] 2. Characterization of each sample
[0087] The electron microscope image (SEM image) of HE-LDH / CNT prepared in Example 1 is as follows: Figure 2 As shown, compared Figure 2 and Figure 1 It can be known that in Figure 2 HE-LDHs clusters can be clearly seen in the figure.
[0088] In addition, the EDS and EDX elemental images of HE-LDH / CNT prepared in Example 1 are as follows: Figure 3 As shown, the corresponding EDX elemental maps confirmed the uniform distribution of Fe, Al, Ni, Co, Mn, C and O on the CNTs.
[0089] Furthermore, the TEM image of FeAlNiCoMn-HE-LDH / CNT prepared in Example 1 is as follows: Figure 4 As shown, Figure 4(a) TEM image of FeAlNiCoMn-HE-LDH / CNT. The image shows that the FeAlNiCoMn-HE-LDH nanosheet structure is evenly distributed on the CNT. Figure 4 (b) shows clear lattice fringes with a d spacing of 0.230 nm, corresponding to the (015) plane, which is consistent with the XRD results ( Figure 6 The above data show that the present invention successfully synthesized FeAlNiCoMn-HE-LDH nanosheets on the CNT surface, and there are many defects (see Figure 4 (b)), which confirms the formation of crystal dislocations on the high-entropy layered double hydroxide of FeAlNiCoMn-HE-LDH.
[0090] Furthermore, the HAADF-STEM image of FeAlNiCoMn-HE-LDH / CNT prepared in Example 1 is as follows: Figure 5 As shown, Figure 5 (a) and Figure 5 (b) depicts the HAADF-STEM image of FeAlNiCoMn-HE-LDH / CNT and the corresponding EDX elemental map ( Figure 5 (b)) confirmed the uniform distribution of Fe, Al, Ni, Co, Mn, C and O in FeAlNiCoMn-HE-LDH / CNT; the crystalline nature of FeAlNiCoMn-HE-LDH was clearly demonstrated by the selected area electron diffraction pattern ( Figure 5 (b)), Figure 5 (b) shows the selected area electron diffraction (SAED) performed on different particle groups, showing concentric diffraction rings with diffuse bright spots, which indicates that the single crystals and diffuse rings are caused by the presence of carbon material (CNT).
[0091] Furthermore, the electron microscopy images of HE-LDHs prepared in Comparative Example 1 are as follows: Figure 6 As shown, the electron microscope image of AlNiCoMn prepared in Comparative Example 2 is as follows Figure 7 As shown, the electron microscope image of AlNiCo prepared in Comparative Example 3 is as follows Figure 8 As shown, the electron microscope image of AlNi prepared in Comparative Example 4 is as follows Figure 9 As shown, the electron microscope image of FeNi prepared in Comparative Example 5 is as follows Figure 10As shown above. From the above, it can be seen that LDH-structured nanosheets were successfully synthesized for various samples (HE-LDHs, AlNiCoMn, AlNiCo, and AlNi), and the morphology of all LDHs was the same. However, only in the case of FeAlNiCoMn-HE-LDH / CNT prepared in Example 1, the nanosheet structure of FeAlNiCoMn-HE-LDH was uniformly distributed on the surface of the carbon nanotubes, and the nanosheet LDH was uniformly distributed, while in the other LDHs (HE-LDHs, AlNiCoMn, AlNiCo, and AlNi), they were aggregated. Therefore, MWCNT was used as a dispersion of LDH structure.
[0092] Furthermore, the crystal structures of FeNi-LDH, FeAlNiCoMn-HE-LDH and FeAlNiCoMn-HE-LDH / CNT samples were examined by XRD analysis. Figure 11 As shown in Figure 2, the results show that all samples show peaks at 2θ values of 11.704°, 23.5181°, 27.0275°, 34.5583°, 39.1084°, 46.7485°, 56.3136° and 60.0446°, corresponding to the (003), (006), (012), (015), (018), (110) and (018) planes; the above data illustrate the formation of single-phase FeNi-LDH and indicate that the high entropy material formation; and, there is a strong peak at 11.704°(003), which is consistent with the formation of layered double hydroxide (LDH); in addition, the relative intensity of all peaks of FeNi-LDH is stronger and higher than that of FeAlNiCoMn-HE-LDH and FeAlNiCoMn-HE-LDH / CNT, which indicates that the crystal size and crystallinity of binary LDH are larger than those of FeAlNiCoMn-HE-LDH and FeAlNiCoMn-HE-LDH / CNT.
[0093] The peak of FeAlNiCoMn-HE-LDH / CNT is broader than that of FeNi-LDH and FeAlNiCoMn-HE-LDH, which indicates that the particle size of FeAlNiCoMn-HE-LDH / CNT is smaller than that of FeNi-LDH and FeAlNiCoMn-HE-LDH. This is because the high surface area of MCNT facilitates the dispersion of FeAlNiCoMn-HE-LDH nanosheets on MWCNT, and the peak at 27.0275° is related to the graphitic carbon of MWCNT.
[0094] Furthermore, the porous properties of FeAlNiCoMn-HE-LDH and FeAlNiCoMn-HE-LDH / CNT nanocomposites were tested by nitrogen adsorption test (BET test instrument). The nitrogen isothermal adsorption-desorption curve and BET specific surface area diagram are shown in Figure 2. Figure 12 The results show that the isotherm is convex at low pressure, indicating a strong affinity between the adsorbate and the adsorbent. The average pore size, average pore volume and BET surface area of FeAlNiCoMn-HE-LDH and FeAlNiCoMn-HE-LDH / CNT are shown in Table 1.
[0095] Table 1 BET surface area, average pore diameter and average pore volume
[0096]
[0097] As can be seen from Table 1 above, the high entropy layered double hydroxide (HE-LDH / CNT) supported by carbon nanotubes prepared in Example 1 has improved BET surface area, average pore size and average pore volume compared with the HE-LDHs prepared in Comparative Example 1. The average pore size is increased by 9.4%, the average pore volume is increased by 495.7%, and the specific surface area is increased by 16.03%.
[0098] 2. Electrochemical test
[0099] In the present invention, electrochemical data measurements (except for the OER performance test) were performed at room temperature using an electrochemical analyzer (BioLogic SP-300); an atypical three-electrode system was used with nickel foam (NF) as the working electrode, a saturated calomel electrode (SCE) as the reference electrode, (E(RHE) = E(measured potential) + E(SCE) + 0.059) * pH), where the pH after calibration was (13-14) and E(SCE) = 0.241 V), and a graphite rod as the counter electrode. The catalyst ink was prepared by dispersing 8.0 mg of FeAlAlNiCoMn-HE-LDH / CNT (also known as FeAlNiCoMn / CNT) in 1 ml of ethanol and 5% Nafion (0.02 mL), followed by ultrasonication for 30 minutes to form a uniform ink. The prepared ink was dropped onto the surface of a 1 cm long and 0.5 cm wide nickel foam electrode (cleaned with ethanol and 1.0 M HCl before loading the ink), resulting in a uniform ink of approximately 1 mg / cm 2 After purging with 1.0M KOH solution and O2 at 25 °C for about 30 minutes to remove dissolved oxygen from the solution, linear sweep voltammetry measurements were performed in 1.0M KOH with a scan rate of 2 mVs -1 In the present examples, all potentials are relative to the reversible hydrogen electrode (RHE), and the polarization curves of all catalysts are obtained similarly.
[0100] (1) OER performance test
[0101] The FeAlAlNiCoMn-HE-LDH / CNT prepared in Example 1, the FeAlNiCoMn prepared in Comparative Example 1, the AlNiCoMn prepared in Comparative Example 2, the AlNiCo prepared in Comparative Example 3, the AlNi prepared in Comparative Example 4, and the IrO2 provided in Comparative Example 6 were subjected to OER performance tests. The LSV diagrams of the OER performance tests of different samples are shown in FIG. Figure 13 As shown, the results show that FeAlNiCoMn-HE-LDH / CNT has the lowest overpotential among all samples, highlighting its efficiency and applicability.
[0102] (II) Sweep voltammetry curve, Tafel slope, electrochemical impedance spectrum and the effect of scan rate (pH 13-14)
[0103] The linear sweep voltammetry (LSV) curves of FeAlAlNiCoMn-HE-LDH / CNT prepared in Example 1, FeAlNiCoMn prepared in Comparative Example 1, IrO2 provided in Comparative Example 6, and Bare NF provided in Comparative Example 7 are shown in FIG. Figure 14 As shown in Figure 2, the results show that the OER mass loading in 1.0 M KOH solution is approximately 1 mg cm -2 The electrochemical performances of FeAlNiCoMn-HE-LDH (FeAlNiCoMn), FeAlNiCoMn-HE-LDH / CNT and IrO2 catalysts were evaluated. The overpotentials from lowest to highest were FeAlNiCoMn-HE-LDH / CNT, FeAlNiCoMn-HE-LDH and IrO2, respectively; the increases in current density from highest to lowest were IrO2, FeAlNiCoMn-HE-LDH and FeAlNiCoMn-HE-LDH / CNT, respectively, which indicated that FeAlNiCoMn-HE-LDH / CNT had the most significant oxygen evolution efficiency.
[0104] In addition, the Tafel slopes of FeAlAlNiCoMn-HE-LDH / CNT prepared in Example 1, FeAlNiCoMn prepared in Comparative Example 1, IrO2 provided in Comparative Example 6, and Bare NF provided in Comparative Example 7 (the Tafel slope is the smallest when the electrochemical desorption OER process occurs, and the electrocatalytic performance is the best) are as follows: Figure 15 As shown, the results show that the Tafel slope of FeAlNiCoMn-HE-LDH / CNT is 46.65mV / dec, which is the smallest, indicating that it has the best electrocatalytic performance and the strongest activity for OER in 1.0MKOH alkaline solution, and is greater than that of precious metal catalysts such as IrO2.
[0105] Furthermore, the FeAlAlNiCoMn-HE-LDH / CNT prepared in Example 1, the FeAlNiCoMn prepared in Comparative Example 1, the IrO2 provided in Comparative Example 6, and the Bare NF provided in Comparative Example 7 were subjected to EIS (AC impedance is also called electrochemical impedance spectroscopy, the frequency range of electrochemical impedance spectroscopy (EIS) is 0.01 Hz to 100 kHz; the amplitude of the interfering AC potential applied during the test is 10 mV; the scanning potential range of the potentiodynamic polarization curve is ±0.3 V vs. Ecorr (relative to the self-corrosion potential); the scanning rate is 1 mV / s)
[0106] The charge transfer resistance of the sample was further analyzed at an overpotential of 10 mV. Figure 16 As shown, the results show that the LSV and EIS of FeAlNiCoMn-HE-LDH, FeAlNiCoMn-HE-LDH / CNT, IrO2, CNT, Bare NF, AlNI-LDH, FeNi-LDH, AlNiCo-LDH, FeNiCo-LDH, FeAlNiCoMn-LDH, AlNiCoMn-LDH were obtained at an overpotential of 10 mV and a frequency of 10 MHz to 100 kHz, and it was concluded that FeAlNiCoMn-HE-LDH / CNT had the lowest overpotential;
[0107] And, the corresponding fitting data recorded by the Nyquist plot of electrochemical impedance are listed in Table 2, where Rs is the bulk solution resistance, Rct represents the charge transfer resistance of the electrolyte and electrode, CPE is the constant phase element, and a1(Fs)^ (a.l) Represents the double-layer capacitor electrode / solution interface. The radius of the semicircle in the Nyquist plot is related to the charge transfer resistance of the evolving reaction; the semicircle with the shortest radius corresponds to the lowest charge transfer resistance and the fastest electron transfer reaction.
[0108] Table 2 Electrochemical impedance spectroscopy fitting data
[0109] catalyst Rs(Ohm) CPE <![CDATA[a1(F.s)^ (a.l) ]]> Rct(Ohm) FeAlNiCoMn-HE-LDH / CNT 1.46 0.025 0.72 7.10 FeAlNiCoMn-HE-LDH 1.46 0.0098 0.820 16.00 <![CDATA[IrO2]]> 1.46 0.0095 0.855 38.26 Bare NF 1.47 0.0095 0.855 371.34
[0110] It can be seen from Table 2 above that the order of Rct from highest to lowest is FeAlNiCoMn-HE-LDH, FeAlNiCoMn-HE-LDH / CNT, IrO2 and pure nickel metal foam (BareNF), which indicates that FeAlNiCoMn-HE-LDH / CNT has the fastest electron transfer reaction rate.
[0111] Furthermore, the effects of scan rate (the effective surface area of the catalyst was calculated by measuring its double layer capacitance, which was determined by constructing cyclic voltammetry (CV) and plotted at potentials in the range of 0.98 V to 1.08 V versus RHE of 10-100 mVs-1) on the FeAlAlNiCoMn-HE-LDH / CNT prepared in Example 1, the FeAlNiCoMn prepared in Comparative Example 1, the IrO2 provided in Comparative Example 5, and the BareNF provided in Comparative Example 6 (pH 13-14) are shown. Figure 17 The results show that the double layer capacitance effective surface area (ECSA) of FeAlNiCoMn-HE-LDH / CNT, FeAlNiCoMn-HE-LDH and pure nickel metal foam (BareNF) are 6.21mF / cm 2 , 5.06mF / cm 2 and 2.94mF / cm 2 Among them, FeAlNiCoMn-HE-LDH / CNT has the largest double-layer capacitance effective surface area.
[0112] (3) Stability test
[0113] The FeAlNiCoMn-HE-LDH / CNT prepared in Example 1 was subjected to a stability test (also called a durability test, the test was carried out in a 1.0 M KOH solution with a constant current of 10 mA cm -2 and 150mAcm -2 The results are shown in Table 1. Figure 18 As shown, the results show that at 150mAcm -2 At an extremely high current density of 1.5 Å, the electrocatalytic performance of FeAlNiCoMn-HE-LDH / CNT remains good for an ultra-long duration of about 240 hours.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should all be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing a porous carbon nanotube-supported high entropy alloy, characterized in that: include: (1) mixing a multi-walled carbon nanotube dispersion with a mixed metal salt to obtain a mixed solution, wherein the mixed metal salt is composed of iron nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate; (2) mixing the mixed solution, urea and ammonium fluoride to obtain a reaction precursor solution; (3) subjecting the reaction precursor solution to a hydrothermal reaction at 110° C. to 150° C. to obtain a porous carbon nanotube-supported high entropy alloy; The porous carbon nanotube-supported high-entropy alloy is a porous nanoflower network structure; the nanosheet structure formed by iron, aluminum, nickel, cobalt and manganese elements is evenly distributed on the surface of the multi-walled carbon nanotubes; and the average pore size of the porous carbon nanotube-supported high-entropy alloy is 10nm-11nm, and the average pore volume is 0.25cm 3 / g-0.3cm 3 / g, specific surface area is 50m 2 / g-54m 2 / g, the effective surface area of the double layer capacitor is 6.2mF / cm 2 -6.5mF / cm 2 , the Tafel slope is 46mV / dec-47mV / dec.
2. The method for preparing a porous carbon nanotube-supported high entropy alloy according to claim 1, characterized in that: The multi-walled carbon nanotubes in the multi-walled carbon nanotube dispersion are oxidized multi-walled carbon nanotubes.
3. The method for preparing a porous carbon nanotube-supported high entropy alloy according to any one of claims 1 or 2, characterized in that: The molar ratio of the mixed metal salt to urea is (5.8-6.2):1, and the molar ratio of the mixed metal salt to NH4F is (2.3-2.7):
1.
4. The method for preparing a porous carbon nanotube-supported high entropy alloy according to any one of claims 1 or 2, characterized in that: In the mixed solution, the molar concentrations of iron nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate are all 0.5mmol / L-1mmol / L.
5. The method for preparing a porous carbon nanotube-supported high entropy alloy according to claim 4, characterized in that: In the mixed metal salt, iron nitrate, nickel nitrate, cobalt nitrate, manganese nitrate and aluminum nitrate are present in equal molar amounts.
6. The method for preparing a porous carbon nanotube-supported high entropy alloy according to any one of claims 1, 2 or 5, characterized in that: The mass ratio of the multi-walled carbon nanotubes to the mixed metal salt is 1:(50-80).
7. The method for preparing a porous carbon nanotube-supported high entropy alloy according to any one of claims 1, 2 or 5, characterized in that: The hydrothermal reaction time is 10h-18h.
8. The method for preparing a porous carbon nanotube-supported high entropy alloy according to any one of claims 1, 2 or 5, characterized in that: The method also includes a purification step, which includes: washing the porous carbon nanotube-supported high-entropy alloy obtained by the hydrothermal reaction with a detergent, and then vacuum drying it in a vacuum drying oven at 40° C.-60° C. for 10 h-15 h.
9. Use of the porous carbon nanotube-supported high entropy alloy prepared by the method for preparing the porous carbon nanotube-supported high entropy alloy according to any one of claims 1 to 8 as a catalyst in oxygen evolution reaction by electrolysis of water.
Citation Information
Patent Citations
Carbon-supported metal catalyst and preparation method and application thereof
CN112536043A
FeCoNiMnCr high-entropy alloy / high-entropy oxide heterogeneous phase catalyst as well as preparation method and application thereof
CN115261921A